TINGKAT KEPUASAN PASIEN TERHADAP MUTU PELAYANAN KESEHATAN GIGI DAN MULUT PADA PRAKTIK MANDIRI TERAPIS GIGI DAN MULUT TAHUN 2023 - .Regita Artamevia; Ni Nengah Sumerti; Anak Agung Gede Agung; Ni Wayan Arini (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2023)
Patient satisfaction is the patient's response to the suitability of the level of interest or patient expectations before they receive dental and oral health services with after the dental and oral health services they receive. The purpose of this study was to determine the level of patient satisfaction with dental and oral health services in the independent practice of dental and oral therapists in Peguyangan Village, North Denpasar District. The method in this research is descriptive survey method, the number of respondents is 30 people. The results of 30 respondents indicated the tangibles dimension, all of the sub dimensions obtained the criteria of very satisfied as much as 83%, from the dimension of reliability showed that all of the sub dimensions obtained the criteria of very satisfaction as much as 73%, from the responsiveness dimension indicated that all of its sub dimensions obtained the criteria of very satisfaction as much as 77%, from the assurance dimension showed that all of its sub dimensions obtained the criteria of very satisfaction, the dental and oral therapist sub staff were skilled in carrying out their duties as well as polite and friendly sub-services obtaining the criteria of very satisfied as much as 80%, and from the empathy dimension it showed that all sub dimensions obtained very satisfied criteria of 60%. From the results of the study it can be concluded that all dimensions of satisfaction, including tangibles, reliability, responsiveness, assurance, and empathy are considered very satisfied with the services received.